Infrared temperature sensing - Noor Jamin, Muhammad Anwar; Abdul Rahim, Ruzairi; Ahmad, Anita; Abdul Rahim, Herlina; Abas, Khairul Hamimah (Penerbit UTHM, 2016)
In the field of temperature sensing, there are any ways to measure a temperature on both living and non-living things. Nowadays, temperature was able to be measured by using the infrared radiation. Infrared (IR) is invisible radiant energy, electromagnetic radiation with longer wavelengths than those of visible light, extending from the nominal red edge of the visible spectrum at 700 nanometers (frequency 430 THz) to 1 mm (300 GHz)[1]. Infrared thermography (IRT), thermal imaging, and thermal video are examples of infrared imaging science. Thermo graphic cameras usually detect radiation in the long infrared range of the electromagnetic spectrum (roughly 9,000–14,000 nanometers or 9–14 μm) and produce images of that radiation, called thermograms. The principle of the infrared thermal imaging was by receiving the invisible infrared radiation energy which emitted by the object into the air. Based on the relationship between the infrared radiation energy and temperature could know the relevant object surface temperature (Stefan-Boltzmann Law)[2][3].